The world according to Humphrey - Birney, Betty G. (New York : Puffin Books, 2005)
Humphrey, pet hamster at Longfellow School, learns that he has an important role to play in helping his classmates and teacher.
Booklist
Publisher's Weekly
School Library Journal
4.2
3-6
3-6
Keywords: Hamsters -- Fiction; Pets -- Fiction; Schools -- Fiction; Hamsters -- Fiction; Pets -- Fiction; School stories